ANTIBIOTICS USAGE OVERVIEW IN ORTHOPEDIC SURGERY PATIENTS AT A HOSPITAL IN BALI - Putu Ary Pudak Wangi; Made Krisna Adi Jaya (Journal Pharmaceutical Science and Application, 2022)
Backgrounds: Antibiotic resistance can be prevented by controlling the use of antibiotics wisely. Based on WHO recommendations, controlling the use of antibiotics is done by grouping antibiotics with the AWaRe category. Objective: This work aims to present an overview of the use of antibiotics in orthopaedic surgery patients as an effort to monitor the use of antibiotics in a hospital in Bali. Methods: Based on the patient's medical record data, the antibiotics used for orthopaedic surgery were calculated and grouped with the AWaRe classification. Results: Results showed that the most prescribed antibiotic was ceftriaxone (84.74%). There were no antibiotics in the reserve category, but the highest percentage was 94.92% in the watch category, and the access category was 5.08%. Conclusion: There is still non-selective use of antibiotics in this hospital, so in the future, it is necessary to evaluate qualitatively and quantitatively to ensure rational use as well as efforts to prevent the occurrence of antibiotic resistance. Keywords: Antibiotics; Resistance; AwaRe; Hospital; Bali